Is Receptor-Interacting Protein Kinase 3 a Viable Therapeutic Target for Mycobacterium tuberculosis Infection? - Stutz, Michael D.; Ojaimi, Samar; Ebert, Gregor; Pellegrini, Marc (Frontiers in Immunology, 2018)
The dwindling list of antimicrobial agents exhibiting broad efficacy against clinical strains of Mycobacterium tuberculosis (Mtb) has forced the medical community to redefine current approaches to the treatment of tuberculosis. Host receptor interacting protein kinase 3 (RIPK3) has been flagged recently as a potential target, given that it is believed to regulate necroptosis-independent signaling pathways, which have been implicated in exacerbating several inflammatory conditions, and which reportedly play a role in the necrosis of Mtb-infected macrophages. To examine the therapeutic potential of inhibiting RIPK3, we infected RIPK3-deficient mice with aerosolized Mtb. We found that the loss of RIPK3 did not alter overall disease outcomes, with deficient animals harboring similar bacterial numbers in the lungs and spleens compared to their wild-type counterparts. Mtb-infected macrophages were not rescued from dying by Ripk3 deletion, nor did this affect production of the proinflammatory cytokine IL-1b, both in vitro and in vivo. Infiltration of immune cells into the lungs, as well as the activation of adaptive immunity, similarly were not overtly affected by the loss of RIPK3 signaling. Collectively, our data argue against a role of RIPK3 in mediating pathological inflammation or macrophage necrosis during Mtb disease pathogenesis, and thus suggests that this host protein is unlikely to be an attractive therapeutic target for tuberculosis.